Gender differences in endurance performance and training
Comparison of the of the three critical components of endurance performance - maximal oxygen consumption, lactate threshold and efficiancy, between men and women. Summary: Of the three critical components of endurance performance the only one that is clearly and consistently depressed in females is the maximal oxygen consumption. Further comparisons are made between muscular strength and anaerobic power, psychological status, training.